Dual-stimuli-responsive TiOx/DOX nanodrug system for lung cancer synergistic therapy. Issue 39 (14th June 2018) - Dai, Zideng; Song, Xue-Zhi; Cao, Junkai; He, Yunping; Wen, Wen; Xu, Xinyu; Tan, Zhenquan
Abstract : TiO x /DOX nanosheets are synthesized and used as a novel nanodrug system, which introduces new possibilities to improve the efficacy of cancer by the synergistic therapy of chemotherapy and radiotherapy. Abstract : Biological applications of nanosheets are rapidly increasing currently, which introduces new possibilities to improve the efficacy of cancer chemotherapy and radiotherapy. Herein, we designed and synthesized a novel nano-drug system, doxorubicin (DOX) loaded titanium peroxide (TiO x ) nanosheets, toward the synergistic treatment of lung cancer. The precursor of TiO2 nanosheets with high specific surface area was synthesized by a modified hydrothermal process using the polymer P123 as a soft template to control the shape. TiO x nanosheets were obtained by oxidizing TiO2 nanosheets with H2 O2 . The anti-cancer drug DOX was effectively loaded on the surface of TiO x nanosheets. Generation of reactive oxygen species, including H2 O2, ·OH and ·O2 −, was promoted from TiO x nanosheets under X-ray irradiation, which is effective for cancer radiotherapy and drug release in cancer cells. In this way, chemotherapy and radiotherapy were combined effectively for the synergistic therapy of cancers. Our results reinforce the DOX loaded TiO x nanosheets as a pH sensitive and X-ray controlled dual-stimuli-responsive drug release system. The cytotoxicity, cellular uptake, and intracellular location of the formulations were evaluated in the A549 human non-small cell lung cancer cell line. Our results showed that TiO x /DOX complexes exhibited a greater cytotoxicity toward A549 cells than free DOX. This work demonstrates that the therapeutic efficacy of DOX-loaded TiO x nanosheets is strongly dependent on their loading mode and the chemotherapeutic and radiotherapy effect is improved under X-ray illumination, which provides a significant breakthrough for future applications of TiO x as a light activated drug carrier in cancer chemotherapy and radiotherapy.